2007
DOI: 10.1111/j.1440-1681.2007.04848.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Is an Important Component of Airway Inflammation in Mice Exposed to Cigarette Smoke or Lipopolysaccharide

Abstract: 1. It was proposed previously that oxidative stress is a main component of the inflammatory process in chronic obstructive pulmonary disease (COPD). Thus, in the present study, we investigated the inflammatory response in mice deficient for the p47(phox) subunit of NADPH oxidase (p47 KO) exposed to cigarette smoke (CS). 2. Exposure of mice to CS elicited an increase in the number of macrophages and neutrophils and levels of interleukin (IL)-6, keratinocyte-derived chemokine (KC/CXCL1) and monocyte chemoattract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…In one study (150), the number of macrophages and neutrophils and levels of IL-6, keratinocyte-derived chemokine (KC/CXCL1), and MCP1/ CCL2 in BALF were lower in p47phox…”
Section: Nox2 As a Target For Drug Developmentmentioning
confidence: 94%
“…In one study (150), the number of macrophages and neutrophils and levels of IL-6, keratinocyte-derived chemokine (KC/CXCL1), and MCP1/ CCL2 in BALF were lower in p47phox…”
Section: Nox2 As a Target For Drug Developmentmentioning
confidence: 94%
“…The lung responses in p47phox-and NOX2-null mice were associated with increased production of proinflammatory cytokines and chemokines via a TLR4-NF-kB pathway, indicating that NOX2 may mediate anti-inflammatory functions by restraining TLR4 activation (Yao et al, 2008). However, another group reported that p47phox-null mice have less inflammation, IL-6, keratinocytederived chemokine, and monocyte chemoattractant protein-1 in lung-lavage specimens after cigarette-smoke exposure compared with wild-type mice (Lagente et al, 2008). The differences observed by these groups may be due to variability in lung compartment sampling, cellular distributions, and chronicity of cigarette-smoke exposure.…”
Section: Dbnp366mentioning
confidence: 95%
“…Therefore, the biological function of NADPH oxidase enzymes might be attributable to the production of ROS. 31 ROS have been shown to mediate the expression of VCAM-1 and ICAM-1. 8 Most of TNF-␣ actions are elicited by TNFR1, which contains a death domain that fosters protein-protein interactions, particularly with other death-domain proteins.…”
Section: Discussionmentioning
confidence: 99%